contestada

Rewrite the function by completing the square. f(x)= 2 x^{2} +13 x +20f(x)=2x 2 +13x+20f, left parenthesis, x, right parenthesis, equals, 2, x, squared, plus, 13, x, plus, 20 f(x)=f(x)=f, left parenthesis, x, right parenthesis, equals (x+(x+left parenthesis, x, plus )^2+) 2 +right parenthesis, squared, plus

Respuesta :

Answer:

  • f(x) = 2(x + 13/4)² - 9/8

--------------------

Given

  • Function f(x) = 2x² + 13x + 20

Rewrite it by completing the square

  • f(x) =
  • 2x² + 13x + 20 =
  • 2(x² + 13/2 x) + 20 =
  • 2[x² + 2x*13/4 + (13/4)² - (13/4)²] + 20 =
  • 2(x + 13/4)² - 169/8 + 20 =
  • 2(x + 13/4)² - (169 - 8*20)/8 =
  • 2(x + 13/4)² - 9/8

Answer:

[tex]f(x)=2\left(x+\dfrac{13}{4}\right)^2-\dfrac{9}{8}[/tex]

Step-by-step explanation:

Given function:

[tex]f(x)=2x^2+13x+20[/tex]

Factor out 2 from the terms in x:

[tex]f(x)=2\left(x^2+\dfrac{13}{2}x\right)+20[/tex]

Add the square of half the coefficient of x inside the parentheses, and subtract the distributed equivalent outside the parentheses:

[tex]f(x)=2\left(x^2+\dfrac{13}{2}x+\left(\dfrac{\frac{13}{2}}{2}\right)^2\right)+20-2\left(\dfrac{\frac{13}{2}}{2}\right)^2[/tex]

Simplify:

[tex]f(x)=2\left(x^2+\dfrac{13}{2}x+\left(\dfrac{13}{4}\right)^2\right)+20-2\left(\dfrac{13}{4}\right)^2[/tex]

[tex]f(x)=2\left(x^2+\dfrac{13}{2}x+\dfrac{169}{16}\right)+20-\dfrac{169}{8}[/tex]

[tex]f(x)=2\left(x^2+\dfrac{13}{2}x+\dfrac{169}{16}\right)-\dfrac{9}{8}[/tex]

Factor the perfect trinomial inside the parentheses:

[tex]f(x)=2\left(x+\dfrac{13}{4}\right)^2-\dfrac{9}{8}[/tex]

ACCESS MORE